ANALYSIS OF CONTINGENCY LEADERSHIP AND SITUATIONAL LEADERSHIP ON JOB SATISFACTION THROUGH WORK MOTIVATION AS A MEDIATING VARIABLE - Wulansari, Febi; Ramdan, Asep Muhamad; Nurmala, Resa (Islamic Management: Jurnal Manajemen Pendidikan Islam, 2025)
This study examines the effect of contingency leadership style and situational leadership on job satisfaction with work motivation as a mediating variable. The phenomenon of the problem raised is the low job satisfaction of employees at Altha Medika Dua Clinic Sukabumi, which can have a negative impact on productivity and service quality. This study aims to analyze the extent to which the two leadership styles affect job satisfaction and the role of work motivation in this relationship. The research method used was a quantitative method with a survey approach using questionnaires distributed to 30 employees of Altha Medika Dua Clinic Sukabumi. The data analysis technique used Structural Equation Modeling (SEM) with the PLS program. The data collected included primary data from questionnaires and secondary data from literature studies. The results showed that both contingency leadership and situational leadership had a positive and significant influence on job satisfaction. In addition, work motivation is proven to mediate the relationship between contingency and situational leadership on job satisfaction. Work motivation itself also has a significant influence on job satisfaction. These results indicate the importance of adaptive and situational leadership and increased work motivation to improve employee job satisfaction at Altha Medika Dua Clinic Sukabumi.